Multiple logics and accounting mutations in the Italian National Health Service. Issue 1 (April 2017) - Anessi-Pessina, Eugenio; Cantù, Elena
Highlights: In Continental Europe, the traditional public-administration logic is re-emerging. Where mature and legitimized, accruals accounting systems will not be repealed. However, mutations will be introduced to draw them closer to cash accounting. The focus will be on nation-wide consolidated statements to control public finances. Faithful representation of individual organizations will be overshadowed. Abstract: Traditional public administration (PA) relied on cash- or commitment-based budgets, while NPM advocated accruals accounting. Currently, Continental Europe is witnessing the re-emergence of the PA logic, but the relevant accounting implications have been insufficiently investigated. We focus on the Italian National Health Service. Our findings suggest that accruals accounting will not be repealed. However, accounting mutations will be introduced to increase consistency with the PA logic and budgetary accounting. Accruals accounting numbers will be interpreted and used accordingly. Great attention will be paid to nation-wide consolidated statements for the control of public finances, while faithful representation of individual organisations will be overshadowed.